Incidence, risk factors and management of pleural effusions during dasatinib treatment in unselected elderly patients with chronic myelogenous leukaemia. Issue 2 (19th July 2012) - Latagliata, Roberto; Breccia, Massimo; Fava, Carmen; Stagno, Fabio; Tiribelli, Mario; Luciano, Luigiana; Gozzini, Antonella; Gugliotta, Gabriele; Annunziata, Mario; Cavazzini, Francesco; Ferrero, Dario; Musto, Pellegrino; et al.
Abstract To assess the most important features and clinical impact of pleural effusions, which are a common toxicity during dasatinib treatment and often impair its high efficacy, 172 unselected consecutive patients with chronic myelogenous leukaemia in chronic phase treated in 27 Italian centres, with dasatinib when aged >60 years for resistance/intolerance to imatinib, were examined. During treatment, 52/172 patients (30.2%) presented pleural effusion, which was grades 1–2 in 38 patients and grades 3–4 in 14 patients (8.1% of the entire cohort of patients), according to the WHO scale; in 14/52 patients (26.9%), there was a concomitant pericardial effusion. Pleural effusion was recurrent in 25/52 patients (48.0%). Median time from dasatinib to first pleural effusion was 11.0 months (interquartile range 3.6–18.6). Eleven patients (6.4%) required permanent dasatinib discontinuation. Only presence of concomitant pulmonary disease ( p = 0.035) and initial daily dose of dasatinib (140 mg vs 100 mg, p = 0.014) were significantly associated with pleural effusions. There were no differences among patients with or without pleural effusions as concerns response rates and overall survival. Pleural effusions were common in our unselected 'real‐life' population of elderly patients but were clinically manageable and did not seem to affect treatment results. Copyright © 2012 John Wiley & Sons, Ltd.